Sugar and the 2002 U.S. Farm Bill - Jose Alvarez; Robert A. Gilbert (EDIS)
This is EDIS document SC 056, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2002. This publication is also part of the Florida Sugarcane Handbook, an electronic publication of the Department of Agronomy, University of Florida, Gainesville, FL.